Implementation of statistical process control in small and medium enterprise industry - Mohd Khairul Rizal, Abd. Halim (2009)
This project has undertaken analysis and report on the Statistical Process Control (SPC) in Chaudry Textiles (Malaysia) Sdn Bhd, a manufacturing company. The objectives of this project are to implement SPC technique in printing process, to analyzed data of printed fabric and give some recommendations from the study of SPC. By using SPC tools specially the and R chart and process capability study which is the Cp and Cpk indices in this particular study, variation due to assignable causes in the process has been identified where the 4M; Men, Machines, Methods, and Materials, causes become the main source of variation. The Cp index show how well the process spread is compared to the specification spread and the Cpk index shows whether the process is producing reject or not. Analysis has showed that the printing process for the production of cotton fabric is in-control. The Cp index value is 1.51 which is more than 1.00, the pattern on the control chart showing the unnatural process where many points in a row fell below the centerline. The Cpk index value is 1.19 and showing the process is in control but the printing process is not consistent. Prevention action and countermeasure are proposed in order to get the process back on its target based on the effect of the 4M